A system development methodology for embedded applications - Goh, Kiah Mok (Cranfield University, 2009)
In recent years, Singapore’s manufacturing sector has contributed more than a quarter of the total Gross Domestic Product (GDP) and has established global leadership positions in several manufacturing areas such as electronics, Information Technology (IT) and industrial automation. The Singapore Economic Review Committee (ERC) recommendation states that “software and embedded systems that drive products are one of the most important technologies for the manufacturing sector. “ With the increasing adoption of automated and intelligent products, embedded systems have emerged as a crucial technology for Singapore. However, the development of embedded applications is not a trivial undertaking as it can usually involve multi-discipline parties and different application platforms. Most embedded application developments use either vendor specific or desktop based methodologies. Vendor specific methodologies constrain the company to rely on the specific vendor's solutions, whereas desktop-based methodologies are not well suited to embedded application development. Therefore, this research aims to develop a standard-based system development methodology for embedded applications. The research programme comprises 5 stages. The first stage reviews the existing system development methodologies for embedded applications. The next stage formulates the proposed conceptual methodology followed by the development of the proof-of-concept tool to demonstrate the merits of the proposed approach. The methodology is then tested and evaluated respectively by using industrial experiments and feedback from a workshop. The final stage refines the methodology based on the feedback and presents the final system development methodology. The research has provided a sound foundation which future research in methodology for embedded applications to develop further.